2000
DOI: 10.1080/03079450020016841
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin E-1 (colistin sulphate) (neuro-)intoxication in young ostriches ( Struthio camelus spp.)

Abstract: Colistin (polymyxin E) is a cyclic polypeptide with a potent bactericidal action against most gramnegative bacilli. When used parenterally, polymyxins should be given with great care as they have a very small safety range, and easily induce neurotoxicity and nephrotoxicity. A dose of 39.5 mg/kg body weight colistin sulphate injected subcutaneously induced rapid (within 1 to 3 h) mortality in young ostriches. Clinical signs of apathy, lethargy and hypotonia indicative of neurotoxicity of the compound were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…An early study of the safety of intramuscularly administered colistimethate sodium (CMS) indicated that 7.3% of the patients developed neurotoxicity during the first four days of therapy [14]; mild neurotoxicity (such as paresthesias) may be more frequently, especially for the elderly patients, but it was usually ignored because of lake of objective assessment [15,6,8,16]. Multiple animal studies, have shown that colistin can induce neurotoxicity in mice [1718], rats [19], pigs [20] or ostriches [21]. Notably, our mouse model studies demonstrated that high doses (15 mg/kg/day for 3 or 7 days) of colistin administered intravenously can cause marked neurotoxicity and neuronal in damage the brain [17,15].…”
Section: Discussionmentioning
confidence: 99%
“…An early study of the safety of intramuscularly administered colistimethate sodium (CMS) indicated that 7.3% of the patients developed neurotoxicity during the first four days of therapy [14]; mild neurotoxicity (such as paresthesias) may be more frequently, especially for the elderly patients, but it was usually ignored because of lake of objective assessment [15,6,8,16]. Multiple animal studies, have shown that colistin can induce neurotoxicity in mice [1718], rats [19], pigs [20] or ostriches [21]. Notably, our mouse model studies demonstrated that high doses (15 mg/kg/day for 3 or 7 days) of colistin administered intravenously can cause marked neurotoxicity and neuronal in damage the brain [17,15].…”
Section: Discussionmentioning
confidence: 99%